2017
DOI: 10.1002/pd.5028
|View full text |Cite
|
Sign up to set email alerts
|

Elevation of glycosaminoglycans in the amniotic fluid of a fetus with mucopolysaccharidosis VII

Abstract: Objective The aim of this study was to quantify GAGs in amniotic fluid (AF) from an MPS VII fetus compared with age-matched fetuses obtained from normal pregnancies. Method Disaccharides were measured by liquid chromatography tandem mass spectrometry (LC/MS/MS), compared to age-matched controls. Enzyme assay was performed in AF supernatant or cultured amniocytes. GUSB was analyzed by next generation sequencing using Ion Torrent Personal Genome Machine with a customized panel. Results No activity of β-glucu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 56 publications
0
15
0
Order By: Relevance
“…The early identification of MPS affected newborns remains challenging since most of them do not exhibit any signs of the disease early in life [23]. However, considering that several studies demonstrated that GAGs are elevated as early as 21 weeks of gestation [9,24], we strongly believe that newborn screening will be a useful tool to identify patients before the onset of irreversible signs and symptoms associated with the disease. We described herein, the development and validation of a UPLC-MS/MS multiplex method, which allows an absolute quantification of HS, DS and creatinine, and is suitable for newborn screening of MPS I, II, III, VI, and VII using urine DUS from 21-day-old newborns.…”
Section: Discussionmentioning
confidence: 99%
“…The early identification of MPS affected newborns remains challenging since most of them do not exhibit any signs of the disease early in life [23]. However, considering that several studies demonstrated that GAGs are elevated as early as 21 weeks of gestation [9,24], we strongly believe that newborn screening will be a useful tool to identify patients before the onset of irreversible signs and symptoms associated with the disease. We described herein, the development and validation of a UPLC-MS/MS multiplex method, which allows an absolute quantification of HS, DS and creatinine, and is suitable for newborn screening of MPS I, II, III, VI, and VII using urine DUS from 21-day-old newborns.…”
Section: Discussionmentioning
confidence: 99%
“…To quantify GAGs in different matrices, liquid chromatography tandem mass spectrometry has been used [48]. GAGs can be quantified in: urine [34,[49][50][51][52][53][54], serum/plasma [34,48,[54][55][56], dried blood spots [57][58][59] (Figure 3), amniotic fluid [60], cerebrospinal fluid [34,61], cultured cells [34], and tissues [62]. Some of these assays can be used for newborn screening of MPSs [57,63] or even to allow the discrimination of specific disease subtypes [53].…”
Section: Biomarkersmentioning
confidence: 99%
“…β-glucuronidase is an essential lysosomal enzyme that participates in the later steps of the catabolism of multiple species of GAG polysaccharides and proteoglycans. Recessively inherited loss-of-function mutations in GUSB causes the mucopolysaccharidosis Sly's syndrome (MPS VII) (Heuer et al, 2001;Kubaski et al, 2017;Kyle et al, 1990;Paigen, 1989;Ray et al, 1999;Zielonka et al, 2017). Prior ChIPseq data from human K562 cells demonstrates that THAP1 is bound to the GUSB promoter ( Fig.…”
Section: Thap1 Binds To and Regulates The Gusb (Mps Vii) Gene Encodinmentioning
confidence: 99%